Antibiotic resistance among Aerobic Gram-Negative Bacilli isolated from patients with oral inflammatory dysbiotic conditions—a retrospective study - Basic, A.; Blomqvist, S.; Charalampakis, G.; Dahlén, G. (Frontiers in Dental Medicine, 2024)
Introduction Aerobic gram-negative bacilli (AGNB) are not part of the resident oral microflora but are occasionally found in high abundance under inflammatory dysbiotic conditions at various oral niches. The aim of the present study was to investigate the identity and antibiotic susceptibility of AGNB isolated from patients in Sweden with mucosal lesions, periodontitis, and peri-implantitis, with special attention to antibiotic resistance and on the presence of phenotypic Extended Spectrum Beta-Lactamase (ESBL) isolates. Materials and methods Microbiolgical samples were harvested from 211 patients in total, experiencing mucosal lesions (N = 113), periodontitis (N = 62), or peri-implantitis (N = 36). The growth of AGNBs was semiquantified by selective and non-selective culture and the strains were isolated, identified, and tested for antibiotic susceptibility. A total of 251 AGNB strains, occurring in moderate to heavy growth (>100 CFU/ml sample), indicating a dysbiotic microbiota, were identified. The disc diffusion method was used for screening of the antibiotic susceptibility of the isolates. Phenotypic identification of ESBL isolates was based on resistance to ceftazidime and/or cefotaxime. Results The most commonly detected AGNB isolates in oral inflammatory dysbiotic conditions were fermentative species belonging to Enterobacteriaceae e.g. Citrobacter spp., Enterobacter spp., Escherichia coli, Klebsiella spp, and the non-fermentative environmental Burkholderia cepacia, Pseudomonas spp., and Stenotrophomonas maltophilia. No clear trends were seen in frequency of the various species in samples from mucosal lesions, severe periodontitis, and peri-implantitis cases. The 138 Enterobacteriaceae isolates and 113 environmental AGNB isolated showed a high antibiotic resistance in general against antibiotics commonly used in dentistry (Amoxicillin, Amoxicillin + Clavulanic acid, Ampicillin, Clindamycin, Doxycycline, Erythromycin, Oxacillin, PenicillinV, and Tetracycline). The majority of these isolates were susceptible to ciprofloxacin. Ten isolates (4.1%) were phenotypically classified as ESBL positive. The ESBL isolates were predominantly found among isolates of S. maltophilia, while only one ESBL positive isolate was found among Enterobacteriaceae. Conclusions Phenotypically identified ESBL isolates can occasionally be present among oral AGNB strains isolated in abundance from the dysbiotic microbiota occurring in cases with oral mucosal lesions, severe periodontitis, or peri-implantitis.